A Comparison of Veterans Who Repeat Versus Who Do Not Repeat a Course of Manualized, Cognitive-Behavioral Therapy for Posttraumatic Stress Disorder. Issue 6 (November 2017) - Schumm, Jeremiah A.; Pukay-Martin, Nicole D.; Gore, Whitney L.
Abstract: Despite evidence that cognitive-behavioral therapy (CBT) for posttraumatic stress disorder (PTSD) is effective, some individuals do not experience clinically significant reduction or remission of their PTSD symptoms. These individuals may return for additional PTSD-focused psychotherapy. However, there is no research to know whether PTSD treatment repeaters have worse symptoms prior to the initial treatment episode or display differences in other pretreatment characteristics versus nonrepeaters. Research is also needed to explore whether treatment repeaters exhibit PTSD symptom changes during an initial or second course of treatment. The current study examines differences in pretreatment characteristics and treatment response among U.S. military veterans who participated in either a single course ( n = 711) or in two separate courses ( n = 87) of CBT for PTSD through an outpatient Veterans Affairs PTSD treatment program. Veterans completing two courses of CBT for PTSD were more likely to be married and employed and more likely to drop out of their initial course of treatment versus those who completed a single course. Hierarchical linear models showed that reductions in PTSD symptoms during treatment were not different for those who completed a second versus single course of CBT for PTSD. However, for those participating in two courses of CBT for PTSD, a relapse in PTSD symptoms was observed between the first and second course. These findings show that a second course of CBT may be viable for those with ongoing PTSD symptoms. Highlights: Participants were U.S. veterans with posttraumatic stress disorder Manualized, cognitive-behavioral therapy was provided as part of routine care Demographic differences were found for treatment repeaters vs. nonrepeaters Repeaters vs. nonrepeaters did not differ on symptom improvement Repeating therapy may benefit some individuals with posttraumatic stress disorder